Economic analysis of buffer preparation strategy for single-use bioprocessing of monoclonal antibodies - Takao ITO; Ann-Kathrin Uebele; Takashi Nihei; Koichi Yamamoto; Naoto Watanabe; Yoshiyuki Tokieda; Masaki Okada (EFB Bioeconomy Journal)
The total cost of buffer preparation was analyzed for an existing single-use mAbs downstream processing facility. The cost effectiveness of outsourcing the liquid buffer as a ready-to-use and/or concentrate was examined by comparing a traditional made-in-house buffer from solid ingredients. The analysis show the combination of made-in-house buffer and concentrate buffer provides the greatest cost advantages. Ready-to-use buffers are more effective for improved facility footprint and provide cost benefits when in-house labor and consumables exceeds the cost of outsourcing. From the calculation of the cost of labor and number of pallets, although the difference in labor costs was small between the various buffer preparation methods, the use of concentrated buffers reduced both the total number of pallets and overall costs. When a new in-line dilution system is installed, a high facility utilization rate of at least ten preparations per year is required to leverage the cost savings from single-use consumables.